Hemodynamic Response to Gabapentin in Conscious Spontaneously Hypertensive Rats - Behuliak, Michal; Bencze, Michal; Polgárová, Kamila; Kuneš, Jaroslav; Vaněčková, Ivana; Zicha, Josef (Hypertension (Dallas, Tex., 2018)
Ligands of auxiliary α2δ subunit of voltage-dependent calcium channels (VDCCs) decrease elevated L-type VDCCs surface expression in arterial myocytes and arterial constriction in spontaneously hypertensive rats (SHR). However, their effect on blood pressure (BP) is unclear. In this study, we investigated the hemodynamic response to acute and chronic administration of gabapentin, a ligand of auxiliary α2δ subunit of VDCCs, in adult SHR with established neurogenic hypertension. The acute gabapentin administration lowered BP and heart rate more in conscious SHR than Wistar-Kyoto rats. Both nifedipine (L-type VDCCs blocker) and ω-conotoxin GVIA (N-type VDCCs blocker) also decreased BP more in SHR, but only gabapentin and ω-conotoxin GVIA abolished the nitroprusside-induced reflex tachycardia of baroreceptor-heart rate control. Hypotensive effect of gabapentin was accompanied by a reduction of (1) plasma norepinephrine level, (2) depressor response to ganglionic blocker pentolinium, (3) power of low frequency component of systolic BP variability, and (4) pressor response of mesenteric vascular bed to periarterial nerve stimulation, suggesting the decrease of peripheral sympathetic nerve transmission. Moreover, gabapentin effects on BP and baroreflex were absent in sympathectomized rats. In conclusion, the acute (but not chronic) administration of gabapentin lowered BP more in SHR than in Wistar-Kyoto rats. Besides the known L-type VDCCs involvement in the vascular effect of gabapentin, our data revealed the important role of N-type VDCCs in acute gabapentin effect on sympathetic control of BP. Gabapentin-induced changes of sympathetic nerve transmission indicated major hemodynamic mechanism of the acute response to this drug.
Keywords: Consciousness; Blood Pressure; Hypertension; vápníkové kanály - typ L; blokátory kalciových kanálů; Heart Rate; Rats, Inbred SHR; zvířata; Calcium Channels, N-Type; Rats, Inbred WKY; Species Specificity; calcium channels; Sympathetic Nervous System; srdeční frekvence; vědomí; mužské pohlaví; gabapentin; Calcium Channel Blockers; sympathectomy; Calcium Channels, L-Type; Gabapentin; baroreflex; sympathetic nervous system; hypertenze; analgetika; druhová specificita; potkani inbrední SHR; nifedipin; Nifedipine; sympatický nervový systém; Animals; Male; vápníkové kanály - typ N; potkani inbrední WKY; Analgesics; krevní tlak